The effect of independent commissioners, EVA, and ROA on firm value - Wijaya, Jessica; Radianto, Wirawan Endro Dwi (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2023)
The rising number of companies listed on the Indonesia Stock Exchange (IDX) each year reflects a growing trend of public companies in Indonesia. Investment in the manufacturing sector escalated from IDR 272.9 trillion in 2020 to IDR 325.4 trillion in 2021. This research aims to measure influence of the number of independent commissioners, Economic Value Added (EVA), and Return on Assets (ROA) on firm value. Multiple regression analysis is used as the method of analysis, and sampling is done using purposive sampling. The total sample consists of 202 samples from 45 consumer goods sector companies for the period of 2015-2019. The results of this research indicate that the number of independent commissioners, EVA, and ROA have a significant influence on the value of consumer goods sector companies registered on the Indonesia Stock Exchange (IDX) for the period of 2015-2019. This highlights the importance of ROA and EVA that can impact firm value and the role of independent commissioners in running a company.